Growth and Yield Response of Rodent Tuber (Typhonium flagelliforme (Lodd.) Blume) under Different Light Intensities and Concentrations of Paclobutrazol - Utami, Noorwitri; Devy, Lukita; Arianto, Arief (Jurnal Jamu Indonesia, 2016)
Rodent tuber (Typhonium flagelliforme (Lodd) Blume) is one of the medicinal plants used for anticancer treatment, but the information on the cultivation of the plant is limited. The objectives of this research was to study the effect of light intensity and concentration level of paclobutrazol on growth and yield of rodent tuber. This research was conducted at Puspiptek Serpong, Tangerang Selatan, Indonesia. This experiment arranged in a split plot design with three replications. The main plot is light intensity (35, 55, and 100%). The sub plot is concentration level of paclobutrazol (0, 50, 100, and 150 ppm). Paclobutrazol applied as soil drench at one month after planting. In each application 500 ml solution was used. Variables observed consisted of plant height, number of leaves, leaf length, leaf width, leaf and tuber fresh weight; and leaf and tuber dry weight. Data were analyzed using analysis of variance and Duncan Multiple Range test at 5%. The result showed that interaction between light intensity and paclobutrazol affected the whole observed variable. Dry weight of tuber under 35% light intensity was lower than those in other light intensity for all treatments of paclobutrazol. Full sunlight intensity showed better dry weight in all treatments of paclobutrazol. However the dry weight decreasing significantly at 150 ppm paclobutrazol, but still higher than those in 35% light intensity. Therefore, rodent tuber is better cultivated under full sunlight and 55% light intensity with 100 ppm paclobutrazol.